COORDINATION MANAGEMENT ANALYSIS BETWEEN THE PROTOCOL DIVISION AND REGIONAL GOVERNMENT ORGANIZATIONS IN THE IMPLEMENTATION OF THE REGIONAL HEAD'S OFFICIAL AGENDA IN CENTRAL LAMPUNG REGENCY - M. Zuliyan Wahyu Dinata; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
Effective coordination between the Protocol Division and Regional Government Organizations (OPDs) is essential for ensuring the successful implementation of official governmental agendas and maintaining the quality of public administration. However, the increasing complexity of governmental activities often creates coordination challenges related to communication, task synchronization, and institutional collaboration. This study aims to analyze the coordination management between the Protocol Division and OPDs in implementing the official agendas of the Regional Head in Central Lampung Regency. A qualitative approach with a case study design was employed to obtain an in-depth understanding of coordination practices within the local government. Data were collected through in-depth interviews, direct observations, and document analysis involving protocol officers and representatives from relevant OPDs. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while data credibility was ensured through source, method, and time triangulation, as well as member checking. The findings reveal that coordination management is implemented through four interconnected stages, namely planning, implementation, supervision, and evaluation. The Protocol Division serves as the central coordinating unit responsible for integrating the roles and responsibilities of multiple OPDs to ensure the orderly execution of official governmental activities. Effective coordination is supported by leadership commitment, competent human resources, intensive inter-agency communication, and collaborative working relationships. Nevertheless, coordination remains constrained by sudden schedule changes, limited human resources, inconsistent understanding of protocol procedures, and insufficient documentation of evaluation results. This study concludes that strengthening institutional coordination mechanisms, standardizing operational procedures, enhancing staff capacity, and optimizing digital communication systems are essential for improving the effectiveness, responsiveness, and sustainability of protocol management within local government.